Environmental law and contrasting ideas of nature : a constructivist approach - Hirokawa, Keith H. (New York, NY : Cambridge University Press, 2014)
'Law's ideas of nature appear in different doctrinal and institutional settings, historical periods, and political dialogues. Nature underlies every behavior, contract, or form of wealth, and in this broad sense influences every instance of market transaction or governmental intervention. Recognizing that law has embedded discrete constructions of nature helps in understanding how humans value their relationship with nature. This book offers a scholarly examination of the manner in which nature is constructed through law, both in the'hard' sense of directly regulating human activities that impact nature, and in the'soft' manner in which law's ideas of nature influence and are influenced by behaviors, values, and priorities. Traditional accounts of the intersection between law and nature generally focus on environmental laws that protect wilderness. This book will build on the constructivist observation that when considered as a culturally contingent concept,'nature' is a self-perpetuating and self-reinforcing social creation'--
Introduction. Constructing nature through law / Keith H. Hirokawa -- Nature in a constructed world : grounding the constructivist method / Keith H. Hirokawa and Rik Scarce -- An unnatural divide : how law obscures individual environmental harms / Katrina Fischer Kuh -- Defining nature as a common pool resource / Jonathan Rosenbloom -- Property constructs and nature's challenge to perpetuity / Jessica Owley -- Perceiving change and knowing nature : shifting baselines and nature's resiliency / Robin Kundis Craig -- Animals and law in the American city / Irus Braverman -- Boundaries of nature and the American city / Stephen R. Miller -- Constructing nature the radical way : extreme environmentalism and law / Rik Scarce -- Wilderness imperatives and untrammeled nature / Sandra Zellmer -- Native American values and laws of exclusion / Catherine Iorns Magallanes -- Challenging what appears'natural' : the environmental justice movement's impact on the environmental agenda / Shannon M. Roesler -- The transformation of water / A. Dan Tarlock -- Framing watersheds / Craig Anthony (Tony) Arnold -- The last, last frontier / Michael Burger.
Keywords: Environmental law -- United States -- Philosophy; Human ecology; Constructivism (Philosophy)